Pondok Pesantren Sebagai Penguatan Pendidikan Karakter: Tinjauan Filsafat Pendidikan Islam - Saparwadi, Saparwadi (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan Jawa Timur, 2024)
Character education, which has long been discussed and practiced in educational institutions in Indonesia, including Islamic boarding schools, since 2017 is still being studied. This study is an effort to improve character education so that it is not only theorized but becomes a necessity to be practiced consistently. This research uses library research to conclude that strengthening character education in Islamic boarding schools is still considered the most ideal place. Based on the analysis of Islamic educational philosophy, the formal objects of educational value in Islamic boarding schools will provide reinforcement for character education.